ANALISIS MAJAS DAN CITRAAN PADA KUMPULAN LIRIK LAGU GRUP BAND MOCCA ALBUM LIMA - TANIA VIRGIAWAN (PIKTORIAL : Journal of Humanities, 2020)
When reading a text from any language, including text that contains literary texts, poetry, fiction, drama and even song lyrics that are concretely found are languages. An author or writer always puts forward his beautiful ideas so as to produce certain effects for the reader.This research is intended to analyze the language style and images in terms of stylistic studies in the collection of song lyrics of the band Mocca album Lima. The research methodology used is descriptive qualitative method with comprehensive reading and analyzing lyrics.The results of the study that the authors get in the analysis of the lyrics of the Mocca band grub song are the use of contention, comparison, the repetition of sounds at the beginning, middle or end. In adition there are also visual images, motion images, hearing images and feeling images in the collection of lyrics.eywords: Stylistica, Language, Exposition, Image.ABSTRACTWhen reading a text from any language, including text that contains literary texts, poetry, fiction, drama and even song lyrics that are concretely found are languages. An author or writer always puts forward his beautiful ideas so as to produce certain effects for the reader.This research is intended to analyze the language style and images in terms of stylistic studies in the collection of song lyrics of the band Mocca album Lima. The research methodology used is descriptive qualitative method with comprehensive reading and analyzing lyrics.The results of the study that the authors get in the analysis of the lyrics of the Mocca band grub song are the use of contention, comparison, the repetition of sounds at the beginning, middle or end. In adition there are also visual images, motion images, hearing images and feeling images in the collection of lyrics.